PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Siregar, Cindyloisa; Lumban Gaol, Romasi (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to determine the effect of using Corporate Social Responsibility, Profitability (ROA) and Leverage on Tax Aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study was obtained by purposive sampling, with a sample of 39 companies with a period of 3 years so that the total was 117. The analytical method used was multiple linear regression test and hypothesis testing using t test and F test with a rate of 5%. The results of this study indicate that Corporate Social Responsibility (CSR) has no effect on tax aggressiveness, profitability has no effect on tax aggressiveness, and Leverage has a positive and significant effect on tax aggressiveness. Simultaneous test results show that Corporate Social Responsibility (CSR), Profitability and Leverage have a significant effect on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange.Keywords: Corporate Social Responsibility, Profitability, Leverage, Tax Aggressiveness